Analisis Kekuatan Bending Material Komposit Fiber Metal Laminate Serat Kulit Jagung Bermatriks Polyester - Pramudia, Mirza; Prasetyo, Teguh; Mustafa (P3M Politeknik Negeri Cilacap, 2024)
Corn husks contain a significant amount of cellulose, which contributes to enhancing mechanical properties as a reinforcing material in composites, including FML composites. Several studies on composites have shown that corn husk fibers can significantly improve bending strength due to cellulose's strong microfibril structure, which enhances the material's strength and rigidity. In this study, corn husk fibers are used as reinforcement to investigate the effect of varying fiber volume fractions on the bending strength of polyester matrix FML composites. The method employed is hand lay-up, with the composite structure consisting of 1100 aluminum skin, woven roving fiberglass fibers, and natural corn husk fibers. The volume fraction variations used are 5%, 15%, 25%, and 35%. Test results show that bending strength increases with the increase in corn husk fiber volume fraction but decreases at a 35% volume fraction. The highest bending strength is achieved at a 25% corn husk fiber volume fraction, with a value of 108.84 MPa.